Microwave Electronics - Grigoriev, Andrey D. (Springer Series in Advanced Microelectronics,, 2018)
This book describes the physical basis of microwave electronics and related topics, such as microwave vacuum and microwave semiconductor devices. It comprehensively discusses the main types of microwave vacuum and microwave semiconductor devices, their principles of action, theory, parameters and characteristics, as well as ways of increasing the frequency limit of various devices up to the terahertz frequency band. Further, it applies a unified approach to describe charged particle interaction within electromagnetic fields and the motion laws of charged particles in various media. The book is intended as a manual for researchers and engineers, as well as advanced undergraduate and graduate students.